The effectiveness of social rights in household and care employment in Spain from the perspective of the law’s recipient. Some innovations in regulatory provision and means of protection - Vila-Viñas, David (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2023)
The article analyses the domestic and care workers’ sector in Spain. It shows the difficulties of access to social rights and the impact of the covid crisis on their income and access to housing. It analyses the effectiveness of the guarantees of their social rights, both general and more specific: special allowance and a minimum living income. In both areas, problems of effectiveness are identified. This contrasts with the efficacy provided by the self-protection strategies deployed by the domestic workers’ organisations themselves. All this allows us to reflect on the changes that the law must introduce in the categorisation of social groups and in its orientation towards a certain type of subject to recover declining effectiveness.